Inflation and the Competitiveness of Irish Enterprises - Linda Kane; Dermot P. Coates (National Competitiveness and Productivity Council (NCPC), 2022)
Recent increases in global energy and transport prices have increased the cost of doing business for Ireland's enterprises. It is important that the desirable transition to renewable energy sources takes into account the impact of volatile oil and gas prices on Irish enterprises. It remains vital that Ireland protects the competitiveness gains made in recent years, and that we continue to act to address inappropriately high domestic costs which are not matched by corresponding increases in productivity.
Keywords: 330